Glutamine Improves the Growth Performance, Serum Biochemical Profile and Antioxidant Status in Broilers Under Medium-Term Chronic Heat Stress. (3rd September 2019) - Bai, Xi; Dai, Sifa; Li, Jiaqi; Xiao, Shuangshuang; Wen, Aiyou; Hu, Hong
SUMMARY: The aim of the present study was to investigate the effect of glutamine (Gln) on growth performance, biochemical parameters, and antioxidant capacity in broilers exposed to medium-term chronic heat stress. A total of 300 twenty-two-day-old Arbor Acres broilers (half male and female) were randomly divided into 5 groups. The control group was housed at normal temperature (24°C) and fed a basic diet; 4 heat-stressed groups were housed under cyclic high temperature (8 h at 34°C, 16 h at 24°C, daily) and fed the basic diet supplemented with 0, 0.5, 1.0, and 1.5% Gln, respectively. After 2 wk, broilers exposed to high temperature had significantly lower ( P < 0.05) body weight (BW), body weight gain (BWG), feed intake (FI), serum total protein, glutathione (GSH), total superoxide dismutase (T-SOD) activity, and total antioxidant capacity (T-AOC), but higher ( P < 0.05) feed-to-gain ratio (FGR), serum glucose, and malondialdehyde (MDA). Dietary supplementation with 1.0 and 1.5% Gln significantly increased ( P < 0.05) BW, BWG, FI, and serum TP, whereas dietary 1.5% Gln also significantly decreased ( P < 0.05) FGR and serum glucose, compared to the heat treatment control group. Dietary supplementation with 1.0 and 1.5% Gln significantly decreased ( P < 0.05) serum MDA, but significantly increased ( P < 0.05) serum GSH, T-SOD activity, and T-AOC compared to the heat treatment control group. This study suggests that dietary Gln improves growth performance, serum biochemical profile, and antioxidant capacity in heat-stressed broilers.